PENGARUH REWARD DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI KEPALA MADRASAH IBTIDAIYAH SWASTA DI JAKARTA TIMUR - Muhamad Alwi (Jurnal Manajemen Pendidikan, 2013)
The objective of this research is to obtain information concerning effect of reward, and job satisfaction on organizational commitment. The research was carried out by means of survey in East Jakarta, involving 88 principal as respondents who are selected through simple random sampling. This research finding are (1) there is a direct effect reward on organizational commitment. (2) there is a direct effect of reward on job satisfaction. (3) there is a direct effect of job satisfaction on organizational commitment. Therefore, the variation of principal's performance are effected by the variation of reward, variation of job satisfaction, and others variation.